The identity of Endrosis braziliensis Moore, 1883 (Lepidoptera: Oecophoridae, Oecophorinae) - Becker, Vitor O. (SHILAP Revista de lepidopterología, 2024)
The identity of Endrosis braziliensis Moore, 1883 is recognized. Aulonophora Becker, gen. nov. is proposed to accommodate it [Aulonophora braziliensis (Moore, 1883), comb. nov.]. Description and illustrations of adult, genitalia, and larval shelter are presented.